Prognostic Relevance of Estrogen Receptor Status in Circulating Tumor Cells in Breast Cancer Patients Treated With Endocrine Therapy - Zhou, Ying; Zhou, Jinmei; Xiao, Jinyi; Wang, Yuehua; Wang, Hao; Shi, Haoyuan; Yue, Chunyan; Jia, Fei; Li, Ping; Hu, Zhiyuan; Yang, Yanlian; Jiang, Zefei; et al. (Frontiers in Oncology, 2022)
Recently, female breast cancer (BC) has surpassed lung cancer to occupy the first place of the most commonly diagnosed cancer. The unsatisfactory prognosis of endocrine therapy for breast cancer might be attributed to the discordance in estrogen receptor (ER) status between primary tumors and corresponding metastases, as well as temporal and spatial receptor status heterogeneity at point-in-time between biopsy and treatment. The purpose of this study was to evaluate the prognostic and predictive value of ER status in circulating tumor cells (CTCs) in BC patients. We analyzed ER expression on CTCs isolated using the Pep@MNPs method in 2.0 ml of blood samples from 70 patients with BC and 67 female controls. The predictive and prognostic value of ER expression in CTCs and immunohistochemistry results of biopsies for progression-free survival (PFS) and overall survival (OS) of patients in response to therapies were assessed. The detection rate for CTCs was 95.71% (67/70 patients), with a median of 8 CTCs within 2 ml of peripheral venous blood (PVB). A concordance of 76.56% in ER status between CTCs and corresponding primary tumor and 69.23% between CTCs and corresponding metastases was observed. We also found that patients with ER-positive CTCs (CTC ER+) had longer PFS and OS than those without ER-positive CTCs (CTC ER-). Our findings suggested that ER status in CTCs of BC patients may provide valuable predictive and prognostic insights into endocrine therapies, although further evaluation in larger prospective trials is required.